Implementation of Digital Adaptive Hysteresis Current Control Technique - Bakan, A. Faruk; Dudak, A. Talha (IEEE, 2017)
Current control performance and stability are very important in motor drive, UPS, active filter and PV inverter applications. Designing a current controller is a time consuming work. Control analysis is required to ensure stable operation and to improve dynamic response. However, such detailed analysis is not needed in the hysteresis current control method. The hysteresis method is an analog-based simple method. This method has a high dynamic response and very good stability compared to other current control methods. However, the method is not widely used because of the variable switching frequency. Variable switching frequency causes difficulty in filter design and EMI problems in some applications. In this study, the problems encountered in hysteresis current control are investigated and a method is presented to solve these problems. The effects of the parameters used in band calculation are simulated in detail. With the developed digital current control method constant frequency is maintained.
Keywords: BAND CURRENT CONTROL; SWITCHING FREQUENCY; INVERTERS; MODULATION; PREDICTION; VSI; Engineering